A combined strategy for improving productivity and well-being: Mitigating the damage of a high stress culture in the construction industry. Issue 9 (9th September 2019) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: This research paper uncovered that the leading causes of stress among construction professionals are work and information dependency, receiving inadequate information, and receiving poor quality information. The construction industry's grueling work culture can be improved by management setting more realistic budgets and timescales, by companies training construction professionals in effective teamwork and stress management strategies, and through deploying information management technology to set effective communication standards. Originality/value: The briefing saves busy executives, strategists and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.